Students’ chosen learning style in the modern technology era - Djuria Suprato (Candradimuka: Journal of Education, 2025)
The new era after Covid-19 pandemic has shifted students’ learning style. Students are facing another learning style than they knew before (traditional or face to face). This study aims to describe students' perceptions of learning style in new era after pandemic. This research used a descriptive quantitative method. The number of respondents was 56 participants. The data collection technique in this study used a questionnaire distributed in the form of a Google form regarding student perceptions of the application of online English learning. The results of this study indicate that most students are interested in online learning. Online learning is considered to be more fun and flexible. In terms of the platform that is the medium for implementing online learning itself, the WhatsApp and Microsoft Teams application is considered the best or dominant application and is very helpful for online learning during the pandemic. Therefore, this data proves that the research respondents had positive perceptions of online learning during the Covid-19 pandemic and also can be applied for now.